2021
DOI: 10.3892/etm.2021.10665
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates angiotensin II‑induced cardiomyocyte hypertrophy by upregulating the MuRF1 and MAFbx pathway

Abstract: Pathological cardiac hypertrophy induced by aging and neurohumoral activation, such as angiotensin II (Ang II) activation, is an independent risk factor for heart failure. The muscle really interesting new gene-finger protein-1 (MuRF1) and muscle atrophy F-box (MAFbx) pathway has been previously reported to be an important mechanism underlying the pathogenesis of cardiac hypertrophy. Metformin is currently the first-line blood glucose-lowering agent that can be useful for the treatment of cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…To this end, we used IMR90-hiPSCs-derived CMs to identify here a microgravity-controlled axis causing a senescence-like phenotype leading to contractile dysfunctions in CMs. To get evidence that SMG may induce also atrophy of the CMs, we investigated the effects of SMG on the expression of three genes MurF1 , FOXO and SMAD3 that serve as markers for cardiomyocytes atrophy ( Du et al., 2021 ; Ni et al., 2006 ; Tsui et al., 2015 ; Xin et al., 2017 ). As indicated in Figure S4 the, expression of all three genes was significantly upregulated in comparison to c-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we used IMR90-hiPSCs-derived CMs to identify here a microgravity-controlled axis causing a senescence-like phenotype leading to contractile dysfunctions in CMs. To get evidence that SMG may induce also atrophy of the CMs, we investigated the effects of SMG on the expression of three genes MurF1 , FOXO and SMAD3 that serve as markers for cardiomyocytes atrophy ( Du et al., 2021 ; Ni et al., 2006 ; Tsui et al., 2015 ; Xin et al., 2017 ). As indicated in Figure S4 the, expression of all three genes was significantly upregulated in comparison to c-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for the involvement of MuRF-1 in cardiac fibrosis came from treatment in H9C2 cell lines by metformin enhanced the activity of MuRF1 and demonstrated a reduction in hypertrophic remodeling [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent myocardial hypertrophy leads to myocardial remodeling and left ventricular dilatation, leading to cardiomyopathy, myocardial fibrosis disease, and ultimately heart failure. [3][4][5] In addition, a previous report suggested that myocardial hypertrophy is characterized by an increase in myocardial cell mass and size caused by the activation of hypertrophic markers.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial hypertrophy plays a vital role in the development of CVD, and myocardial hypertrophy is an adaptive response and compensatory phenomenon made by myocardial cells in response to stress after cardiac injury, intending to maintain cardiac output and normal cardiac function. Persistent myocardial hypertrophy leads to myocardial remodeling and left ventricular dilatation, leading to cardiomyopathy, myocardial fibrosis disease, and ultimately heart failure 3–5 . In addition, a previous report suggested that myocardial hypertrophy is characterized by an increase in myocardial cell mass and size caused by the activation of hypertrophic markers.…”
Section: Introductionmentioning
confidence: 99%